The impact of bariatric surgery on macronutrient malabsorption depends on the type of procedure - Evenepoel, Charlotte; Vandermeulen, Greet; Luypaerts, Anja; Vermeulen, Daniel; Lannoo, Matthias; Van der Schueren, Bart; Buyse, Johan; Verbeke, Kristin (Frontiers in Nutrition, 2023)
Bariatric surgery, currently the most effective treatment for patients with morbid obesity, may induce macronutrient malabsorption depending on the type of procedure. Macronutrient malabsorption affects the supply of substrates to the colon, subsequent microbial fermentation and possibly colonic health. Using isotope technology, we quantified the extent of macronutrient and bile acid malabsorption and its impact on colonic protein fermentation in patients after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) and in non-operated controls. Participants consumed a single test meal (day 0) that contained intrinsically labelled (13C, 15N and 2H) egg protein for quantification of protein digestion, malabsorption and fermentation, respectively, together with a transit marker and a marker for bile acid malabsorption. They collected breath samples up to 6h and all urine and stool for 48h and 72h, respectively. Food intake was registered from day -3 to day 2. Malabsorption of fat, protein and carbohydrates differed between groups (p=0.040, p=0.046 and p=0.003, respectively) and was slightly higher in RYGB but not in SG patients compared to controls. Protein fermentation was increased in both patient groups compared to controls (p=0.001) and was negatively correlated to 3H-recovery as a marker of transit (ρ=-0.47, p=0.013). The limited macronutrient malabsorption likely does not affect the nutritional status of the patient. However, the higher protein fermentation may affect colonic health and warrants further investigation.